Prevalence of imported malaria in Parma during 2005-2006 - Peruzzi, S.; Gorrini, C.; Piccolo, et al., G. (Acta Biomedica Atenei Parmensis, 2007)
Background and aim of the work: Malaria is a protozoan infection caused by parasites of the genus Plasmodium (P. falciparum, P. ovale, P. vivax, P. malariae) that is transmitted from one human to another by female Anopheles mosquitoes. It can be considered a reemerging imported disease in our area because of increasing of movements from endemic countries, and nowadays it is the most common imported infection in Italy. This study describes the occurrence of imported malaria in our area between January 2005 and May 2006. Methods: During 17 months we analysed 170 blood samples belonging to 139 patients (95 foreigners and 44 Italians) with the clinical suspect of malaria. Samples were used to prepare orange acridine and Giemsa stained thin blood films for microscopic observation and to perform an immunochromatographic assay for the detection of specific plasmodia antigens. Molecular assays (nested-PCR and Real-time PCR) were also performed in order to confirm the diagnosis. Results: Thirty-six cases of malaria were diagnosed: 35 in foreigners coming from Africa and only one in an Italian who lived in Chad. Thirty-three patients were infected by P. falciparum, 1 by P. ovale, 1 by P. vivax, and a mixed infection by P. falciparum, P. ovale and P. malariae was also found. Conclusions: Malaria is usually associated with travels within areas where the infection is endemic and our data demonstrated that imported malaria in our area has a prevalence of 25.89%.